The Effect of Physical Work Environment on Employee Loyalty at PT Bank Nagari West Sumatra Head Office with Job Satisfaction as a Mediating Variable - Darmansyah, Hilal; Andriani, Chichi (Human Resource Management Studies, 2025)
This study aims to examine: (1) The effect of the physical work environment on employee loyalty, (2) The effect of the physical work environment on job satisfaction, (3) The effect of job satisfaction on employee loyalty, and (4) The effect of the physical work environment on employee loyalty through job satisfaction as a mediating variable at PT Bank Nagari Headquarters in West Sumatra. This research is causal in nature. The population in this study consisted of 153 employees who worked at Bank Nagari Head Office. The study used the total sampling method for sampling. Data were collected through a questionnaire using a Likert Scale as a measuring tool. Data analysis was carried out with the help of SmartPLS 4 software. The results of data analysis in this study indicate that: (1) The physical work environment has a positive and significant effect on employee loyalty in employees of Bank Nagari West Sumatra Head Office (2) The physical work environment has a positive and significant effect on job satisfaction in employees of Bank Nagari West Sumatra Head Office (3) Job satisfaction has a positive and significant effect on employee loyalty in employees of Bank Nagari West Sumatra Head Office (4) The physical work environment has a positive and significant effect on employee loyalty through job satisfaction as a mediating variable in employees of Bank Nagari West Sumatra Head Office.